(untitled) (International Journal of Environmental Sciences, 2025)
The rise of multidrug-resistant pathogens has intensified global interest in traditional medicinal knowledge. This study documented the ethnomedicinal plants used by the B’laan Indigenous community in Lapuan, Davao Occidental, Philippines. Tribal healers and Indigenous experts were interviewed to investigate the ethnomedicinal plants, plant parts used, methods of preparation, ailments treated, and routes of administration. The specimens were collected, pressed, dried, labeled, and identified using taxonomic keys, with confirmation from expert botanists. Quantitative indices, including Use Value (UV), Fidelity Level (FL), and Informant Consensus Factor (ICF), were calculated to assess the frequency and consistency of plant use. The findings reveal a total of 24 plant species belonging to 19 families of ethnomedicinal plants used by the B’laan. Leaves were the most commonly used plant part, boiling was the predominant preparation method, and ingestion was the primary route of administration. Heliotropium indicum L. recorded the highest UV (0.16), primarily used to treat cough, postpartum conditions, sore eyes, and wounds. Six plants, including Curcuma longa L. used for stomach aches, Artemisia vulgaris L. for cough, Momordica charantia L. for diabetes, Gossypium herbaceum L. and Hibiscus rosa-sinensis L. for wounds, and Piper betle L. for dermal itchiness, had FL values of 100%. ICF analysis revealed the highest consensus in treating infectious and parasitic diseases. These findings highlight the B’laan community’s reliance on medicinal plants for primary healthcare. Further research is recommended to preserve their ethnobotanical heritage, explore the pharmacological potential of these species, and encourage similar studies among other Indigenous communities in the Philippines.